Komoditas unggulan tanaman pangan dan pusat pertumbuhan wilayah di Kabupaten Ogan Komering Ulu - Hadikusuma, M. Erry; Rini Efrianti; Yunita Sari (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The potential between sub-districts in Ogan Komering Ulu Regency is different. The superior food crop commodities from each sub-district must be directed towards their development, namely the development of production centers and processing centers. This research is entitled Identification of Leading Food Crops Commodities and Development of Regional Growth Centers in Ogan Komering Ulu Regency which aims to identify and analyze the classification of commodities that have comparative and competitive advantages in each sub-district and identify regional growth centers in each sub-district. The analytical methods used in this research are Location Quotient (LQ) Analysis and Shift Share Analysis and Scalogram Analysis. The results of this study indicate that the development plan to become a center for production and processing of food crop commodities is in 3 sub-districts, namely East Baturaja District, Lubuk Raja District and Sinar Peninjauan District. For the East Baturaja District, the direction of development is to become a production and processing center for corn, cassava and sweet potato commodities. For Lubuk Raja Sub-district, the direction of development is to become a production and processing center for corn, peanut, green beans, cassava and sweet potato commodities. Meanwhile, the Sinar Peninjauan Sub-district has a direction of developing into a production and processing center for lowland rice and cassava commodities.